Analysis of Swallow's Nest Business Income in Kampung Keramat Village, Katingan Kuala District, Katingan Regency - Norlita Norlita (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
The objective of this study was to observe the cost, revenue, business profit and income from Swallow nest in Kampung Keramat Village Katingan Kuala District. This study use quantitative. By using an income analysis , R/C Ratio and Break Event Point. The population in this study are all entrepreneurs of Swallow nest population in Kampung Keramat Village Kecamatan Katingan Kuala, this study use all 23 population by entrepreneurs swallow nest. The result showed average amount for one cycle or equal to three months Rp. 6.786.304, average income obtain Rp. 16.000.000,- for one cycle, average revenue Rp. 9.213.696,- for one cycle. The hypothesis acceptable seen from the result of the analysis R/C ratio more than one, which is 2,35 and BEP (Q) 0.85 kg and BEP (Rp) Rp. 3.393.152,- can be confirmed to reach break even point